1997
DOI: 10.1007/bf02505330
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for primary postpartum haemorrhage

Abstract: The objective of the study was to determine which background factors predispose women to primary postpartum haemorrhage (PPH) at the Obafemi Awolowo University Hospital. The study consisted of 101 women who developed PPH after a normal vaginal delivery and 107 women with normal unassisted vaginal delivery without PPH Both cases and controls were investigated for sociodemographic risk factors, medical and obstetric histories, antenatal events and labour and delivery outcomes. Data were abstracted from the medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 8 publications
6
25
2
Order By: Relevance
“…Consistent with prior studies (30, 31), we found similar risk factors responsible for the primary PPH. However, counts of risk were lower among women in the intervention group indicating that women were more aware about PPH and its risk factors and took necessary precautions accordingly.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with prior studies (30, 31), we found similar risk factors responsible for the primary PPH. However, counts of risk were lower among women in the intervention group indicating that women were more aware about PPH and its risk factors and took necessary precautions accordingly.…”
Section: Discussionsupporting
confidence: 92%
“…Cases of failure of pharmacological correction of bleeding with rFVIIa can be attributed to resistance, for various reasons, of the blood coagulation system to activation of redundant quantity of factor VIIa (Franchini et al, 2007;Selo-Ojeme & Okonofua, 1997;Shander et al,2005;Sobieszczyk & Breborowicz, 2004), as well as by the presence of organ dysfunction, which led to adverse outcome in 6 out of 11 women (54.5%) in our observations.…”
Section: Discussionmentioning
confidence: 56%
“…9 But Babinszki et al showed in their study that incidence of PPH was higher in grand multiparas while Selo-Ojeme and Tsu reported that there is no association between parity and PPH. [10][11] Seventy six cases (56.2%) belonged to lower middle socio-economic status followed by middle socioeconomic status 40 cases (29.6%). Bibi et al showed in their study that patients with lower socio-economic status had more frequency of PPH compared to upper socio-economic status.…”
Section: Discussionmentioning
confidence: 99%